1999
DOI: 10.1177/002215549904701007
|View full text |Cite
|
Sign up to set email alerts
|

Water Channel Protein AQP3 Is Present in Epithelia Exposed to the Environment of Possible Water Loss

Abstract: SUMMARY Aquaporins (AQPs) are membrane water channel proteins expressed in various tissues in the body. We surveyed the immunolocalization of AQP3, an isoform of the AQP family, in rat epithelial tissues. AQP3 was localized to many epithelial cells in the urinary, digestive, and respiratory tracts and in the skin. In the urinary tract, AQP3 was present at transitional epithelia. In the digestive tract, abundant AQP3 was found in the stratified epithelia in the upper part, from the oral cavity to the forestomac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 46 publications
(52 reference statements)
12
127
2
1
Order By: Relevance
“…It was previously known that AQP3 are expressed in large quantities on the basal side of mucosal epithelial cells in the colon (22); however, the results of this study show that AQP3 is expressed on both the apical and basal sides of mucosal epithelial cells in the colon (Fig. 1B).…”
Section: Resultscontrasting
confidence: 64%
“…It was previously known that AQP3 are expressed in large quantities on the basal side of mucosal epithelial cells in the colon (22); however, the results of this study show that AQP3 is expressed on both the apical and basal sides of mucosal epithelial cells in the colon (Fig. 1B).…”
Section: Resultscontrasting
confidence: 64%
“…Alternatively, we hypothesize that AQP3 may function as a part of the membrane osmosensing/mechanosensing system for the initial sensing of cell swelling and therefore, may "trigger" subsequent RVD events such as solute transport and cytoskeleton reconstruction. This hypothesis is supported by the fact that AQP3 is strongly expressed in many organs, such as the bladder, trachea and esophagus, and in olfactory cells [18,28,29] , where they seem to have no obvious requirements for rapid water movement but need sensitive perception of tension, shear stress and so on. Moreover, this hypothesis is supported by the recent discovery that AQP5 is actively involved in salivary gland cell RVD by coordinating with TRPV4, a volume sensitive calcium channel, to concertedly regulate cell volume under hypotonic stimulation [23] .…”
Section: Efficient Sperm Volume Regulation Is a Prerequisite For Normmentioning
confidence: 96%
“…These channels have been identified and shown to play an essential role in diverse physiologic processes, including renal water re-absorption, exocrine gland secretion, and lacrimation. Furthermore, other studies have also shown evidence to support their role in cerebrospinal fluid secretion and re-absorption, generation of pulmonary secretion, and aqueous humour secretion 2,10,22,23,26,28,37) . AQP3 has been reported to be expressed in the kidney, urinary tract, digestive tract, and skin 2,10,22,23,26,28,31,37) .…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, other studies have also shown evidence to support their role in cerebrospinal fluid secretion and re-absorption, generation of pulmonary secretion, and aqueous humour secretion 2,10,22,23,26,28,37) . AQP3 has been reported to be expressed in the kidney, urinary tract, digestive tract, and skin 2,10,22,23,26,28,31,37) . It has been localized in the basal and intermediate cells of stratified squamous epithelia from the fauces to the forestomach and skin 26) , and has also been detected in the suprabasal layer of the oral epithelium during human and mouse tooth development 11,40) .…”
Section: Introductionmentioning
confidence: 94%